2022
DOI: 10.1007/s00216-022-04186-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of methotrexate polyglutamates in human whole blood, erythrocytes and leukocytes collected via venepuncture and volumetric absorptive micro-sampling: a green LC–MS/MS-based method

Abstract: Low-dose methotrexate (MTX) plays a key role in treatment of rheumatoid arthritis. However, not all patients respond satisfactorily, and no therapeutic drug monitoring has been implemented in clinical practice, despite the fact that MTX therapy has now been available for decades. Analysis of individual intracellular MTX metabolites among rheumatoid arthritis (RA) patients is hampered by the low intracellular concentrations of MTX-PGs which require a highly sensitive method to quantify. Here, we present a rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Further comparison was difficult to make as the report by Van Haandel et al 31 did not specify the number of patients with RA, dose of MTX administered, administration route and duration of treatment time. In a recent bioanalytical study with RBCs and PBMCs isolated from eight patients with RA, Daragmeh et al 32 also reported that MTX-PG 1-2 were the major species in PBMCs and that MTX-PGs levels were markedly higher in PBMCs than in RBCs. The authors expressed MTX-PG accumulation values in nmol/L packed cells, which hampers a direct per cell comparison as the mean cell volume (MCV) of RBCs (100 fl) and PBMCs differs substantially (200–400 fl) 37.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further comparison was difficult to make as the report by Van Haandel et al 31 did not specify the number of patients with RA, dose of MTX administered, administration route and duration of treatment time. In a recent bioanalytical study with RBCs and PBMCs isolated from eight patients with RA, Daragmeh et al 32 also reported that MTX-PG 1-2 were the major species in PBMCs and that MTX-PGs levels were markedly higher in PBMCs than in RBCs. The authors expressed MTX-PG accumulation values in nmol/L packed cells, which hampers a direct per cell comparison as the mean cell volume (MCV) of RBCs (100 fl) and PBMCs differs substantially (200–400 fl) 37.…”
Section: Discussionmentioning
confidence: 99%
“…The authors expressed MTX-PG accumulation values in nmol/L packed cells, which hampers a direct per cell comparison as the mean cell volume (MCV) of RBCs (100 fl) and PBMCs differs substantially (200–400 fl) 37. Additionally, Daraghmeh et al did not specify details of patient characteristics, MTX dosing and route of administration to allow a full comparison 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A highly sensitive and specific LC‐MS/MS method was developed for the quantification of methotrexate polyglutamates which are active metabolites of methotrexate. Evaluation of methotrexate polyglutamates in different matrices including plasma, RBCs, peripheral blood mononuclear cells and venous whole blood revealed that VAMS can be used for accurate TDM analysis only if sampling is done immediately before the next dose of methotrexate to ensure that concentrations are not overestimated 28 . In another study in patients with lymphoblastic leukaemia, DPS and wet plasma concentrations of methotrexate were found to have no statistically significant difference 117 .…”
Section: Applicationsmentioning
confidence: 99%
“… 20 Furthermore, paper‐based ionization techniques such as paper spray ionization (PSI) for MS have enabled the direct analysis of a broad spectrum of analytes in dried microsamples without the requirement of any prior sample pretreatment. 21 These sophisticated approaches have driven the implementation of microsampling in various biomedical domains; newborn and metabolic screening, 22 , 23 biomarker research, 21 , 24 , 25 pharmacokinetic (PK) and pharmacodynamic (PD) studies, 26 , 27 therapeutic drug monitoring (TDM), 28 , 29 , 30 , 31 , 32 , 33 forensic toxicology, 34 , 35 , 36 sports anti‐doping, 37 , 38 , 39 metabolomics 22 , 40 , 41 and proteomics. 24 , 42 , 43 Since 70% of medical decisions are governed by diagnostic blood tests, 44 several medical technology companies are investing in the development of innovative at‐home blood microsampling devices to make blood work more accessible and convenient.…”
Section: Introductionmentioning
confidence: 99%